Vilnius University, Department of Archaeology (from 1990 to 2010) - Merkevičius, Algimantas; Remeikaitė, Lijana (Archaeologia Lituana, 2010)
The Department of Archaeology was established in 1940 and later often reorganized, merged with other departments or even closed down. The work of the Department was significantly influenced by the state of political affairs in Lithuania. After Lithuania’s incorporation into the Soviet Union, the archaeological research as well as training of specialists, faced a rather complicated situation. In 1966 the Department was closed down and the Department of the History of the Lithuania SSR was set up by the then autho rities in its place. The Department remained closed during the whole soviet period and was re-established in 1990 under the name of Department of Archaeology and Ethnology. In 1993 it was reorganized and renamed as Department of Archaeology and the speciality of archaeology was then initiated. The aim of this article is to offer a review of the activities of the Department since its restoration until the present day. 1990 was the beginning of a new stage of archaeological research and studies at Vilnius University. Soon after its re-establishment, the Department set up a library and in 1999 publication of a periodical scientific publication “Archaeologia Lituana” was launched, with prof. M. Michelbertas as editor in chief. The Department of Archaeology not only participate but also organize scientific events, such as conferences, symposiums, seminars, etc. The first scientific conference, organized by the re-established Department, took place in 1991. Since 1996 the international conference “In honor of Jonas Puzinas” has been organized on a regular basis. Five scientific conferences of this type have been arranged until now. Other scientific activity, which is not less important, is also pursued. One field of such activity includes participation in scientific projects. The Department have participated in and supervised both national and international projects. At present we have two national projects, namely “ARCHEOLITAS – Compilation and Digitalization of the List of Archaeological Lithuanian Sources”, headed by assoc. prof. A. Luchtanas and “ARCHAEOLANDSCAPE – the Development of the Landscape According to the Archaeological Data and Natural History”, headed by assoc. prof. V. Šimėnas. Assoc. prof. of the Department A. Luchtanas is the research adviser of the international project “The Archaeological – Heritage Preservation Mission in Ghor Province, Afghanistan”. The period of two decades witnessed changes in the field of archaeological studies. In 1991 when the two-level system of bachelor and master studies was approved, the Academic Commission of the Board of Vilnius University projected a number of specializations, one of which was archaeology and ethnology. Two years later, in 1993, a sitting of the Senate of Vilnius University approved initiation of the speciality of archaeology. On 1 September that year 10 students were admitted to the first year course of the speciality of archaeology and since then the number of students has increased to 43. In 1993 Vilnius University also launched a postgraduate programme of archaeology. That same year the Department opened the possibility to maintain doctoral dissertations, which was undertaken not only by the staff of the Department, but also archaeologists of other Lithuanian institutions. By now, a total of 25 doctoral dissertations have been maintained. During the working period of the re-established Department the subject courses and study programmes underwent numerous changes and renewals. Since 1996 archaeology students and lecturers take part in the Erasmus Program in a number of European Universities. Students have the possibility to participate in fieldwork practice in archaeological sites of various types and periods. The number of locations for fieldwork practice has increased from two in 1990 to six-seven. They are headed by the Department lecturers who have carried out investigations at important Lithuanian archaeological sites, such as Kernavė (A. Luchtanas, G. Vėlius), Dubingiai Castle site and the old town of Trakai (A. Kuncevičius), Paragaudis barrow cemetery (M. Michelbertas), flint quarry and flint working site at the Titnas lake (E. Šatavičius), Šereitlaukis settlement and Jašiūnai burial mounds (V. Šimėnas), Stančiai settlement and Jogučiai burial ground (L. Tamulynas), Benaičiai, Turlojiškės and Meškučiai archaeological complex sites (A. Merkevičius). The Department lecturers often travel to lecture abroad. They have lectured at various European Universities. Besides lecturing, the Department staff have been on scholarships and fellowships in various foreign archaeological institutions, where they also collected archaeological evidence and did research work. In cooperation with archaeological institutions of other countries, the Department invites to deliver lectures to foreign archaeologists: Š. Milišauskas (Buffalo University), V. Lang (Tartu University), A. Vasks (University of Latvia), K. Randsborg (Copenhagen University), I. Jansson (Stockholm University), M. Müller-Wille (Ch. Albrecht University), V. Kulakov (Institute of Archaeology of the Russian Academy of Sciences), W. Nowakowski (Warsaw University), R. Mazurowski (Warsaw University), W. Wróblewski (Warsaw University), B. Madsen Gelg (Copenhagen University), M. Geld (The Jagiellonian University of Krakow) and others. Besides scientific and educational activities, the Department is also involved in search for archaeological sites and popularization of archaeology. Every year the researchers present their investigation results to the media. During the last two decades the Department has grown into one of the major archaeological institutions in Lithuania. Changes in Department have a significant impact on the development of the science of archaeology in the country.